Legal Analysis of Criminal Liability of Intellectual Actors in Human Trafficking Crimes Outside the Territory of the Republic of Indonesia - Arif Wahyudi; Korolus K. Medan; Dhesy A. Kase (International Journal Multidisciplinary Science, 2026)
Any person who commits the criminal act of trafficking in persons by bringing Indonesian citizens outside the territory of the Unitary State of the Republic of Indonesia with the intention of exploitation may be held criminally liable under Article 4 of Law Number 21 of 2007 concerning the Eradication of the Criminal Act of Trafficking in Persons. This study aims to analyze issues related to the ambiguity of the term “bringing” as contained in Article 4 of the Law on the Eradication of Trafficking in Persons. The unclear meaning of the term “bringing” is regulated in a limited manner, namely only targeting field perpetrators. This provision has implications for interpreting trafficking in persons committed abroad as only applicable to field perpetrators. The formulation of the problem in this study is how the applicability of Article 4 of the Law on the Eradication of Trafficking in Persons relates to criminal liability for participation in bringing Indonesian citizens abroad for the purpose of exploitation outside the territory of the Republic of Indonesia. The results of the study indicate that the provisions of Article 4 of the Law on the Eradication of Trafficking in Persons, in relation to criminal liability for perpetrators of trafficking in persons outside the territory of the Republic of Indonesia, only impose criminal liability on field perpetrators and not on intellectual actors who serve as the masterminds behind the trafficking crimes committed outside the territory of the Republic of Indonesia. Field perpetrators are considered to have fulfilled the element of “bringing,” such as those who “recruit, pick up, shelter, and transport” victims to destination countries outside the territory of the Republic of Indonesia.